ChemInform Abstract: Azulenophenanthrenes from 2, 2′‐Di(arylethynyl)biphenyls Through C—C Bond Cleavage of a Benzene Ring. Issue 44 (14th October 2013) - Matsuda, Takanori; Goya, Tsuyoshi; Liu, Lantao; Sakurai, Yusuke; Watanuki, Shoichi; Ishida, Naoki; Murakami, Masahiro
Abstract A novel Pt‐catalyzed rearrangement reaction of biphenyls (I) is developed to form azulene derivatives by structural reorganization between the ethyne and arylethyne moieties.